A method to estimate the ice volume and ice-thickness distribution of alpine glaciers - Farinotti, Daniel; id_orcid:0 000-0003-3417-4570; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Bauder, Andreas; id_orcid:0 000-0001-7197-7706; Funk, Martin; Truffer, Martin (Journal of Glaciology, 2009)
ISSN:0022-1430 ISSN:1727-5652